Literasi Keuangan Syariah dan Kemudahan Penggunaan sebagai Determinan Keputusan Menggunakan Mobile Banking Syariah - Sri Rahayu; Nur Eka Setiowati; Yeni Nurkhasanah (Fakultas Ekonomi dan Bisni Islam UIN Siber Syekh Nurjati Cirebon, 2026)
This study aims to analyze and measure the effect of Islamic financial literacy and perceived user convenience on decisions to use Islamic mobile banking. The research method used in this study is quantitative, with data collected through a Google Forms questionnaire. The sampling technique used is Probability Sampling with a random sampling type, the number of respondents is 96 people. The population is Islamic Commercial Bank (BUS) customers who use Islamic mobile banking in Majalengka District. The data analysis used is the research instrument test, classical assumption test, and hypothesis testing. The results showed that Islamic financial literacy (X1) had no significant effect, while perceived user convenience (X2) had a significant effect on the decision to use Islamic mobile banking (Y). Simultaneously, X1 and X2 have a significant effect on Y with a contribution of 78.6%; the remaining 21.4% is influenced by other factors outside this study. The results show that the perception of user convenience is more dominant than Islamic financial literacy, thus providing a strategic contribution to the development of Islamic banking services.